FUNCTIONAL AND SEMANTIC FEATURES OF NUMERALS IN THE STRUCTURE OF PHRASEOLOGICAL UNITS (The Journal of Interdisciplinary Human Studies, 2026)
This article is devoted to the study of the linguocultural, semantic, and ethnolinguistic features of numerals within phraseological units. The research analyzes the denotative and connotative meanings of numerals, their role in reflecting national culture, and the psychological, stylistic, and expressive significance of phraseological units as a whole. Drawing on the theoretical frameworks of Glazunova (2000), Chepasova (1998), Telia (1996), Maslova (2001), Wierzbicka (1992), and Lakoff and Johnson (1980), the study examines how numerals function not merely as grammatical categories but as linguocultural and ethnolinguistic components embedded in the conceptual system of human cognition. By analyzing the universal cultural characteristics of numerals and the emotive-expressive dimensions of numeral-based phraseological units in Arabic, this article contributes to linguocultural, ethnolinguistic, and phraseological research.
Keywords: phraseological units; semantics of numerals; linguoculture; ethnolinguistics; connotation; denotation; emotive-expressive component; Arabic phraseology; cultural symbolism.